Pengembangan Strategi Bisnis Menggunakan Metode Ife, Efe, Qspm, Swot Dalam Mengembangkan Bisnis Pt. Xyz - Patra Caraka dan Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to analyze the external environment of the introduction of products from PT. XYZ and find the strategies that will be used by PT.XYZ to keep sales stable and develop a wider market share using QSPM, SWOT Matrix, IFE matrix, EFE matrix. The source of the data directly comes from observations, questionnaires and interviews. OFF matrix is used to identify internal factors, external companies in the method can know the strengths, weaknesses of opportunities and threats in the company of PT. XYZ.All data from the company will be analyzed and combined to get the strategy that will be used by company to get QSPM strategy. The results of the research will be created to create good opportunities for the company by focusing on the strategy created and creating a low cost strategy.